2019
DOI: 10.1007/s10865-019-00078-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of neuropsychological mechanisms in implementation intentions to reduce alcohol consumption among heavy drinkers: a randomized trial

Abstract: Implementation intention formation, which involves identifying triggers and linking them with coping strategies, has proven effective at reducing alcohol consumption in general populations. For the first time, the present study tested the ability of implementation intentions to reduce alcohol consumption among heavy drinkers and to explore potential neuropsychological mechanisms. At baseline, participants were randomized to form implementation intentions or to an active control group. There was a 5.7 unit (1 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…8,17 Implementation intentions involve creating mental simulations of future events (such as medication taking) that take into account when, where and how to meet behavioral goals and associating these events with cues associated with the action and context of the future event using if-then statements. 8,17,18 Implementation intentions have been shown to improve medication adherence across a variety of medical conditions, 8 and one way in which they may work is by improving prospective memory. 8 Another way to improve PM is Episodic Future Thinking (EFT), [19][20][21] an intervention designed to mentally project oneself into vivid, highly contextual future scenarios.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,17 Implementation intentions involve creating mental simulations of future events (such as medication taking) that take into account when, where and how to meet behavioral goals and associating these events with cues associated with the action and context of the future event using if-then statements. 8,17,18 Implementation intentions have been shown to improve medication adherence across a variety of medical conditions, 8 and one way in which they may work is by improving prospective memory. 8 Another way to improve PM is Episodic Future Thinking (EFT), [19][20][21] an intervention designed to mentally project oneself into vivid, highly contextual future scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] While no research was identified that assessed the effect of implementation intentions on delay discounting in people with poor medication adherence, research has shown that when implementation intentions are used to reduce alcohol consumption, they did not simultaneously improve delay discounting. 18 The current study was an early phase translational science study designed to evaluate EFT effects on medication adherence using a single-case experimental multiple baseline design. 30 Single-case experimental designs are efficient methods for testing new interventions, and for establishing a functional relationship between treatment and outcome changes across multiple dependent measures.…”
Section: Introductionmentioning
confidence: 99%
“…Such an approach lacks precision—it is unclear if implementation intentions reduce both weekly drinking and HED or if effects are limited to one outcome. Second, Malaguti et al's meta‐analysis did not include several recently published studies [ 13 , 14 , 15 ]. Third, effect size differences were calculated on follow‐up differences only, and did not account for group differences in baseline levels of consumption.…”
Section: Introductionmentioning
confidence: 99%